Chronic nausea and vomiting syndrome and impact on quality of life - F.A. Félix-Téllez; J.A. Velarde-Ruiz Velasco; J.M. Aldana-Ledesma; E.S. García-Jiménez; E.C. Morel-Cerda; A.R. Flores-Rendón; J.M. Remes-Troche (Revista de Gastroenterología de México (English Edition))
Introduction and aim: Chronic nausea and vomiting syndrome is a disorder of gut-brain interaction that affects the productive-age population. Our aim was to determine the association of this disorder with quality of life, workplace performance, and socioeconomic impact related to gastrointestinal health. Methods: A cross-sectional study on a Mexican population was conducted. The patients were classified as having chronic nausea and vomiting syndrome or other disorders of gut-brain interaction. A comparative analysis of quality of life, workplace productivity, annual medical consultations, and digestive health-related expenses was carried out, applying a logistic regression model. Results: One thousand patients were included, 79.2% of whom met the criteria for a disorder of gut-brain interaction. Of the 792 patients, 10.3% presented with chronic nausea and vomiting syndrome. Said syndrome was associated with a negative impact on usual activities (OR 4.34, 95% CI 1.90-9.30, p ≤ 0.001), pain/discomfort (OR 2.09, 95% CI 1.31-3.33, p ≤ 0.001), anxiety/depression (OR 2.08, 95% CI 1.30-3.40, p ≤ 0.001), workplace presenteeism (OR 3.96, 95% CI 2.47-6.44, p ≤ 0.001), and workplace absenteeism (OR 2.54, 95% CI 1.52-4.16, p ≤ 0.001). There was also a higher number of annual medical consultations for digestive health (p = 0.013), without generating a greater annual expense due to digestive health (p = 0.08). Conclusions: Chronic nausea and vomiting syndrome produces a negative impact on quality of life, which could be secondary to its symptomatology or its association with anxiety and depression. Resumen: Introducción: El síndrome de náusea y vómito crónico es un trastorno de la interacción cerebro intestino que afecta a la población en edad productiva. El objetivo fue determinar la asociación de este trastorno con la calidad de vida, desempeño laboral e impacto socioeconómico relacionado a la salud gastrointestinal. Métodos: Un estudio de corte transversal en población mexicana. Los pacientes se clasificaron como síndrome de náusea y vómito crónico u otros trastornos de la interacción cerebro intestino. Se realizó un análisis comparativo de la calidad de vida, productividad laboral, consulta médica anual y gastos relacionados a salud digestiva aplicando un modelo de regresión logística. Resultados: Se incluyeron 1000 pacientes, de los cuales 79.2% cumplían criterios de algún trastorno de la interacción cerebro intestino. De los 792 pacientes, 10.3% presentaban síndrome de náusea y vómito crónico. El síndrome de náusea y vómito crónico se asoció a un impacto negativo en las actividades usuales (OR 4.34, IC95%, 1.90-9.30, p = <0.001), Dolor/Malestar (OR 2.09, IC95%, 1.31-3.33, p = <0.001), Ansiedad/Depresión (OR 2.08, IC95%, 1.30-3.40, p = <0.001), presentismo laboral (OR 3.96, IC95%, 2.47-6.44, p = <0.001) y ausentismo laboral (OR 2.54, IC95%, 1.52-4.16, p = <0.001). También presentaron un mayor número de consultas médicas anuales por salud digestiva (p = 0.013) sin generar un mayor gasto anual por salud digestiva (p = 0.08). Conclusiones: El síndrome de náusea y vómito crónico genera un impacto negativo en la calidad de vida, lo que podría ser secundario a su sintomatología o a su asociación con ansiedad y depresión.